2013
DOI: 10.1371/journal.pone.0055085
|View full text |Cite
|
Sign up to set email alerts
|

Glucose 6P Binds and Activates HlyIIR to Repress Bacillus cereus Haemolysin hlyII Gene Expression

Abstract: Bacillus cereus is a Gram-positive spore-forming bacterium causing food poisoning and serious opportunistic infections. These infections are characterized by bacterial accumulation despite the recruitment of phagocytic cells. We have previously shown that B. cereus Haemolysin II (HlyII) induces macrophage cell death by apoptosis. In this work, we investigated the regulation of the hlyII gene. We show that HlyIIR, the negative regulator of hlyII expression in B. cereus, is especially active during the early bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…Instead, it has been shown to be down-regulated by the specific transcriptional regulator HlyIIR [74,75] and by the global regulator Fur [76,77]. The hlyII and hlyIIR genes are present in the same chromosomal locus (Bc 3523 and Bc 3522, respectively, in the ATCC 14579 strain) but are not organized into an operon.…”
Section: Haemolysin IImentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, it has been shown to be down-regulated by the specific transcriptional regulator HlyIIR [74,75] and by the global regulator Fur [76,77]. The hlyII and hlyIIR genes are present in the same chromosomal locus (Bc 3523 and Bc 3522, respectively, in the ATCC 14579 strain) but are not organized into an operon.…”
Section: Haemolysin IImentioning
confidence: 99%
“…It has been suggested that the binding of the appropriate ligand to HlyIIR could change the orientation of the DNA-binding domains, modifying the affinity of the ligand-bound form for the specific DNA site [79]. Consistently, glucose-6-phosphate, a carbon source that is commonly used and consumed by bacteria during their growth [80], binds directly to HlyIIR, increasing its capacity to bind to its DNA box upstream from the hlyII gene, thereby inhibiting its expression [75]. …”
Section: Haemolysin IImentioning
confidence: 99%
“…Although the rationale and mechanism behind the effects of glucose on the phenotype of the Δ secDF mutant remain to be elucidated, this study confirms previous reports showing that glucose exerts more functions than only being an important nutrient. Recent research indicates for instance a direct involvement of glucose in expression of the toxin hemolysin II in B. cereus by activation of HlyIIR by glucose 6P which resulted in repression of hlyII gene expression [83].…”
Section: Discussionmentioning
confidence: 99%
“…in different hosts as illustrated in Figure 1. For instance it was recently reported that G6P is involved in the regulation of the B. cereus virulence factor hemolysin HlyII 36 . Furthermore it would be interesting to investigate the role of the Sps system during infection of B. cereus in other host models and also in other human pathogens, such as B. anthracis , Clostridium species and in insect pathogens like B. thuringiensis or in Paenibacillus .…”
Section: Discussionmentioning
confidence: 99%